2019
DOI: 10.1210/js.2019-00193
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk Profile Among Young Adult Females With a History of Premature Adrenarche

Abstract: Context Premature adrenarche (PA) is associated with childhood overweight and hyperinsulinemia; the long-term cardiometabolic outcome is unknown. Objective To study cardiometabolic profile in adult women with previous PA. Design and participants Thirty women with PA and 41 control subjects were followed from prepuberty to young adulthood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Premature adrenarche has been linked to hyperinsulinaemia and dyslipidaemia during puberty, adolescent presentations of polycystic ovarian syndrome, 44 and increased risk of metabolic syndrome with its significant comorbidity in adulthood, 3 although another recent study did not replicate this. 31 In our study, few participants reported phenotypic pubertal changes despite elevated androgen levels. Hormonal adrenarcheal changes can significantly precede physical changes, and early physical signs can be subtle and difficult to identify.…”
Section: Original Researchmentioning
confidence: 51%
See 1 more Smart Citation
“…Premature adrenarche has been linked to hyperinsulinaemia and dyslipidaemia during puberty, adolescent presentations of polycystic ovarian syndrome, 44 and increased risk of metabolic syndrome with its significant comorbidity in adulthood, 3 although another recent study did not replicate this. 31 In our study, few participants reported phenotypic pubertal changes despite elevated androgen levels. Hormonal adrenarcheal changes can significantly precede physical changes, and early physical signs can be subtle and difficult to identify.…”
Section: Original Researchmentioning
confidence: 51%
“…A follow-up study of the Finnish cohort 29 reported that young women (aged 16.5-23.5 years) who had experienced premature adrenarche continued to show evidence of insulin resistance and had a tendency towards central fat mass distribution, but that cardiometabolic risk factors were no longer associated with adrenarcheal timing (after accounting for BMI across the study population). 31 Further studies examining the long-term impact of adrenarcheal timing and androgen concentrations in late childhood are needed to further explore the trajectories of these risks, including studies of the impact of the normal variability associated with adrenarche as opposed to those diagnosed with premature adrenarche, for whom there are very few data. We found positive relationships between height, weight, BMI, waist circumference and obesity with salivary androgen concentration during adrenarche, in keeping with many previous studies using serum samples 1 32 although others report no association.…”
Section: Discussionmentioning
confidence: 99%
“…As adrenarche and gonadarche frequently overlap, it is clinically not possible to distinguish if pubarche is caused by adrenal or testicular androgens in boys, however, it is likely that pubic hair develops as a consequence of adrenal androgen action in girls. Premature adrenarche has been traditionally regarded as benign variant of normal ‘puberty’, however, there is some evidence suggesting that children with premature adrenarche have metabolic dysfunction, in particular abnormal glucose metabolism ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…As adrenarche and gonadarche frequently overlap, it is clinically not possible to distinguish if pubarche is caused by adrenal or testicular androgens in boys, however, it is likely that pubic hair develops as a consequence of adrenal androgen action in girls. Premature adrenarche has been traditionally regarded as benign variant of normal ‘puberty’, however, there is some evidence suggesting that children with premature adrenarche have metabolic dysfunction, in particular abnormal glucose metabolism (45).…”
Section: Discussionmentioning
confidence: 99%
“…As adrenarche and gonadarche frequently overlap, it is clinically not possible to distinguish if pubarche is caused by adrenal or testicular androgens in boys, however, it is likely that pubic hair develops as a consequence of adrenal androgen action in girls. Premature adrenarche has been traditionally regarded as benign variant of normal 'puberty', however, there is some evidence suggesting that children with premature adrenarche have metabolic dysfunction, in particular abnormal glucose metabolism(45).To assess the dynamics of pubertal development accurately is difficult, both in the individual clinical setting but even more so based on observational studies. Tanner staging is an unequivocally accepted clinical tool to assess pubertal milestones(46), but prone to inter-observer differences(47,48) and over/under estimation of Tanner staging frequently occurs when being self-reported(49).…”
mentioning
confidence: 99%